Circulating bone morphogenetic protein-9 levels are associated with hypertension and insulin resistance in humans - Huang, Hong; Wang, Wei; Yang, Gangyi; Zhang, Yu; Li, Xiaoqiang; Liu, Hua; Zhang, Lin; Zheng, Hongting; Li, Ling (Journal of the American Society of Hypertension, 2018)
It has been demonstrated that bone morphogenetic protein-9 (BMP-9) may have an important role in vascular development and stability. However, the association of circulating BMP-9 with essential hypertension (HTN) has not been established in humans. The objective of this study is to observe the changes of circulating BMP-9 levels in patients with HTN and to investigate the association of circulation BMP-9 and insulin resistance (IR) in a cross-sectional study. Two hundred twenty-five individuals, including 132 patients with hypertension, and 93 healthy controls, were included in the present study. Circulating BMP-9 concentrations were measured with an ELISA kit. The association of circulating BMP-9 with other parameters was analyzed. When compared with healthy subjects, circulating BMP-9 concentrations were markedly lower in HTN patients (46.20 [31.85–62.80] vs. 77.21 [39.33–189.15], P < .01) and correlated negatively with blood pressure and the homeostasis model assessment of insulin resistance (P < .05 or P < .01). Decreasing levels of BMP-9 were independently and markedly related to HTN. In a multiple linear regression analysis, only systolic blood pressure and free fatty acid concentrations were independently associated with circulating BMP-9. Our findings suggest that BMP-9 may be a serum biomarker for HTN and IR. •Circulating bone morphogenetic protein-9 (BMP-9) concentrations were markedly lower in essential hypertension patients compared with healthy subjects.•Systolic blood pressure and free fatty acid were independently associated with circulating BMP-9.•Decreasing levels of BMP-9 were independently and markedly related to essential hypertension.•BMP-9 is a serum biomarker for metabolism-related and insulin resistance–related diseases, including essential hypertension and type II diabetes mellitus.